Studies on modified atmosphere storage of button mushroom using diffusion channel system - Arumuganathan, T; Ramanathan, M; Krishnamoorthy, A S; Rai, R D; Manikantan, M R; Indurani, C; Anandakumar, S (Mushroom Research, 2012)
Button mushroom was stored in diffusion channel storage system, which is a new concept in modified atmosphere storage. PET jars of 7 litre capacity were used as storage chambers and provided with diffusion channels having lengths of 5, 10 and 15 cm and inner diameter of 3, 4 and 5 mm to modify the inside atmosphere. The experiment was conducted to assess the suitability of the system under ambient condition. The quality parameters viz., phenol, protein, total amino acids, total sugars and vitamin - C were analysed for the fresh as well as stored button mushrooms. The quality analysis of all the stored mushrooms showed that the mushrooms stored with 3 mm diameter and 15 cm long diffusion channel for 500 g mushroom was found to be the best combination as compared to all other treatments. By adopting this storage technique, button mushrooms could be effectively stored for 8 days under ambient condition with lowest acceptable change in quality parameters.